Polyarteritis nodosa presented as a dilatation of the intrahepatic bile duct - Choi, Han Lim; Sung, Ro Hyun; Kang, Min Ho; Jeon, Hyun Jeong; Yun, Hyo Yung; Jang, Lee Chan; Choi, Jae Woon; Song, Young Jin; Ryu, Dong Hee (Annals of surgical treatment and research, 2014)
Polyarteritis nodosa (PAN) is a systemic necrotizing vasculitis of small- and medium-sized arteries in multiorgan systems. PAN may affect the gastrointestinal tract in 14%-65% of patients, but rarely involves the biliary tract and liver. We describe a patient without underlying disease who was diagnosed with PAN during resection of the gallbladder and liver.